Development of Brazilian prototypes for child psychodynamic psychotherapy and cognitive-behavioral therapy - Guilherme Pacheco Fiorini; Vera Regina Röhnelt Ramires (Trends in Psychiatry and Psychotherapy)
Abstract Introduction This study developed Brazilian psychodynamic psychotherapy (PDT) and cognitive-behavioral therapy (CBT) prototypes for children with internalizing disorders (ID) and externalizing disorders (ED). Method Eighteen Brazilian experts in PDT (n = 9) and CBT (n = 9) rated the 100 items of the Child Psychotherapy Q-Set (CPQ) describing a hypothetical typical session based on their respective theoretical backgrounds for children with ID. They then rated the same items describing a hypothetical typical session for children with ED. A Q-type factor analysis with varimax rotation was performed. Results Expert correlations were high within each theoretical approach and each diagnostic category. The factor analysis identified three independent factors. CBT ratings concentrated on one factor, while PDT ratings loaded onto one factor describing treatment of children with ID and another factor describing treatment of children with ED. Conclusion The sole CBT prototype reflected a general conceptualization of this approach and was undifferentiated regarding treatment of children with ID and ED. The PDT prototype for children with ID provided evidence of a process focused on interpretation, while the PDT prototype for children with ED characterized a supportive process with attention to the therapeutic relationship. This infers greater variation in the PDT setting for children with different conditions.